House price expectations - Niklas Gohl; Peter Haan; Claus Michelsen; Felix Weinhardt (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This study examines short-, medium-, and long-run price expectations in housing markets. We derive and test six hypothesis about the incidence, formation, and relevance of price expectations. To do so, we use data from a tailored household survey, past sale offerings, satellites, and from an information RCT. As novel findings, we show that price expectations exhibit mean reversion in the long-run. Moreover, we do not find evidence for biases related to individual housing tenure decisions or regret aversion. Confirming existing findings, we show that local market characteristics matter for expectations throughout, as well as aggregate price information. Lastly, we corroborate existing evidence that expectations are relevant for portfolio choice.
Keywords: R21; R31; 330; housing; house price expectations